Cognitive Impairment in Tuberous Sclerosis Complex - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2008)
Seizure histories, EEG recordings and intelligence equivalents and their relation to tuber/brain proportion (TBP) measured by 3 dimensional MRI were evaluated in 61 patients with tuberous sclerosis complex (TSC), in a study at University Medical Center, Utrecht, the Netherlands.